KAJIAN STRUKTURAL PADA PUISI “KEKASIHKU” KARYA JOKO PINURBO - Neng Tuti Novianty (Universitas Maritim AMNI Semarang, 2022)
This article discusses the structural study of the poetry “Kekasihku” by Joko Pinurbo. The focus of the discussion of this article is to describe the physical structure and inner structure of the poetry which is carefully described in the form of words, sentences and discourse. This research method is descriptive qualitative using a structural approach. The data source used as the object of research is one of the poetry contained in the book collection of poetry